EXPLORING THE EVOLUTION OF FAIRNESS TRAITS AMONG STUDENTS: A COMPARATIVE ANALYSIS IN CENTRAL JAVA AND LAMPUNG PROVINCE - Ashari, Mahfud; Lestari, Indah; Zamroni, Edris; Dewi, Pramita Sylvia; Santoso, Santoso; Sucipto, Sucipto (Counsenesia Indonesian Journal Of Guidance and Counseling, 2023)
This research aims to elucidate the evolution of fairness character among students in Central Java and Lampung, while also investigating the impact of the environment on this developmental process. Employing a quantitative descriptive method and ANACOVA test, the researchers examine how the environment (domicile) influences the development of students' fairness character. The data collection encompasses various aspects of fairness character development, as defined by experts, including 1) utilization aspects; 2) appreciation aspect; 3) obedience; and 4) open attitude. The instrument used for assessing fairness character development in students underwent prior testing by experts to ensure alignment with the research subjects' characteristics. The study includes 553 students from Central Java province and 576 students from Lampung province. The research unfolds through stages involving instrument distribution, data collection, and subsequent analysis and interpretation. Results reveal a robust commitment in both Central Java and Lampung to character education, particularly emphasizing fairness. The majority of students demonstrate positive fairness character development. Notably, students in Central Java exhibit stronger characteristics in transparency (open thinking), whereas students in Lampung excel in the attitude aspect aligned with social roles. The development of fairness is intricately linked to the norms and customs prevalent in students' living environments. This underscores the significance of understanding local norms and customs, offering valuable insights for educators. Such insights contribute significantly to fostering fairness character development among students in Central Java and Lampung.